The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s10867-010-9211-7
|View full text |Cite
|
Sign up to set email alerts
|

Torque-induced deformations of charged elastic DNA rods: thin helices, loops, and precursors of DNA supercoiling

Abstract: We study the deformations of charged elastic rods under applied end forces and torques. For neutral filaments, we analyze the energetics of initial helical deformations and loop formation. We supplement this elastic approach with electrostatic energies of bent filaments and find critical conditions for buckling depending on the ionic strength of the solution. We also study force-induced loop opening, for parameters relevant for DNA. Finally, some applications of this nano-mechanical DNA model to salt-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Benham [2,3] and Le Bret [4,5] firstly used the elastic model to analyze the equilibrium configuration of DNA. In the framework of this model, varied subjects related with the DNA configuration were investigated extensively [6][7][8][9][10]. Some geometrical configurations appearing in the DNA condensation have been explained perfectly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benham [2,3] and Le Bret [4,5] firstly used the elastic model to analyze the equilibrium configuration of DNA. In the framework of this model, varied subjects related with the DNA configuration were investigated extensively [6][7][8][9][10]. Some geometrical configurations appearing in the DNA condensation have been explained perfectly.…”
Section: Introductionmentioning
confidence: 99%
“…Some geometrical configurations appearing in the DNA condensation have been explained perfectly. Recently, Cherstvy used the elastic model to further investigate the effect of counterions and attractive inter-segmental DNA-DNA interactions on molecular spatial conformations and the low-dielectric DNA core on the elastic DNA properties [9][10][11] in a micro field. Up to the present, it has been confirmed that the elastic rod model is adequate for characterizing the geometrical configuration and deformation of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The other was to generate a better general understanding, as well as a systematic theoretical analysis, of the role of electrostatic interactions in braided DNA pairs, e.g., as a first step toward studying these effects in supercoiled plasmids. Most previous studies of DNA braiding and supercoiling focused on the topology and mechanics of the double helices (17)(18)(19)(20), although some have included electrostatics (21)(22)(23) by treating DNA as a uniformly charged rod. Recent studies suggest that chiral DNA-DNA interactions may actually play a very important role in DNA braiding and plasmid supercoiling (13,24).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be noted that, this is only a coarse-grained model characterizing interaction potentials between DNA segments and solution, and the deformations of elastic under applied end forces [2,3,10] should be considered in future models.…”
Section: Discussionmentioning
confidence: 99%